Godsdienst in het onderwijs in Zuid-Afrika en Nederland: Een vergelijkende studie - Wolhuter, Charl C. (HTS teologiese studies, 2023)
Religion in education in South Africa and the Netherlands: A comparative study. The aim of this article is the reconstruction and comparison of the historical evolution of the place and role of religion in education in South Africa and in the Netherlands. The article commences with an overview of the historical evolution of the place and role of religion in education, up to the present, and a discussion of the dissatisfaction and objections which could be and which have been levelled against the current situation. The Netherlands has followed a more accommodating policy and practice regarding religious beliefs and diversity than the international norm. While South Africa can learn much from the Dutch approach to the problem of religion in education, this approach has also been challenged in recent times. In both systems, controversy about the accommodation of religion in education has given rise to tension between the notions of freedom, tolerance and accommodation, on the one hand, and the acknowledgement of human rights and the need for social cohesion on the other. Other considerations to be taken into account in this regard are the downsides of providing a partisan, confessional type of education that could hinder learners in maintaining themselves in the outside world. The trend in modern society is towards individualised belief systems, not collective ones. And the warning to be heeded is that the line between education and indoctrination is thin. The current Dutch model, despite the problems that it currently encounters, could provide direction in respect of all these issues.Contribution: The article concludes with an educational-philosophical perspective regarding the question as to how educationists and educators could guide learners to a state where they can independently decide about their personal religious orientation, given the fact that they are now living in a time when relativism prevails, also in terms of religion and faith.